Quality of Life among Patients Undergoing Haemodialysis in Bandung: A Mixed Methods Study - Kustimah Kustimah; Ahmad Gimmy Prathama Siswadi; Achmad Djunaidi; Aulia Iskandarsyah (Faculty of Nursing Universitas Padjadjaran, 2020)
Quality of life (QoL) has become one of important outcome measures of renal replacement therapy, including haemodialysis. However, the assessment of QoL is not comprehensively measured and most research about it use quantitative approach. Since QoL is subjective, assessing and understanding the qualitative evidence are very important. This study aimed to explore QoL in patients with end-stage renal disease (ESRD) undergoing haemodialysis. This research is a cross-sectional study used a mixed method approach. Patients undergoing dialysis were recruited from the dialysis unit in one private hospital in Bandung. They completed the Kidney Disease and Quality of Life (KDQOL-36™) questionnaire and then went on face to face interview. Quantitative data were analysed descriptively and qualitative data were analysed using thematic analysis with qualitative data analysis software. A total of 87 patients completed the questionnaires and 34 of them participated in 20-60 minutes interview. The symptom and problem list had the highest mean score (M= M=63.60), indicated that patients experienced lack of energy, mobility and physical appearance that further produced difficulties in their daily activities. Additionally, mental component summary showed a higher mean score (M=49.23) than the physical component (M=36.22) indicated that patients most likely had worse mental health condition than their general physical health. Worse mental health condition induced with negative feeling among patients. Patient’s inability to do daily activity and change in physical appearance had impact on their confidence for social relationship. Conclusion: ESRD patients undergoing haemodialysis were bothered by the symptom of illness and worsen by the negative feelings.